Local Planning in Libya between Reality and Aspiration - Khoja, Rawasi Hadiya; Wali, Taha Mohamed; Alsari, Fatima Tariq (The annual Scientific Conference for Under and Postgraduate Students at the University., 2024)
The study aims to shed light on the reality of local planning in Libya, and the challenges that may face Libyan local administrations in the local planning process; as for the problem of the study, it examines the relationship between the central administration and the local administration in the issue of planning, this study uses the descriptive analytical approach through which it tries to understand the reality of local planning and explain the obstacles facing local planning in Libya. The study reached a number of results, the most important of which is that the planning experience in Libya was not a successful experience due to the impact of the planning approach by political and economic factors and the absence of community participation, and that the strategy of transformation towards administrative decentralisation in the Libyan model was not clear goals in light of its application in an undemocratic political system and a traditional legal system that is not developed; Also work on updating legislation and adopting the community participation approach in the local planning process.